The status of women and their rights based on the understanding of sisters in Islam; an analysis from an Islamic perspective - Kamaruddin, Zuraidah; Yunus, Saidatolakma; Abdul Rahim, Adibah (IIUM Press, International Islamic University Malaysia, 2018)
The paper aims to analyse the understanding of Sisters in Islam (SIS) on the status of women and their rights from an Islamic perspective. The qualitative approach notably a library research is used to obtain some statements in SIS’ writings in order to further familiarise their perception and understanding towards this issue. Based on the findings, the study reveals that there are several misunderstandings and distortions made by SIS about the status of women and their rights as a result of the improper method of Qur’anic interpretation and lack of referring to the hadith. The using of logic without guidance from the Qur’an and Sunnah also leads to liberal interpretations beyond the limits. The findings of the study demonstrates the true understanding of this issue from an Islamic perspective to the society.